The Relationship Between the Implementation of Multicultural Education and the Development of Intercultural Awareness in A Socio-Geographic Context - Agnes Setianingsih; Julia Kumala Asri Drakel; Mely Tri Octavina; Putri Tipa Anasi; Rohana Sufia (International Journal of Geography, Social, and Multicultural Education, 2024)
The need for multicultural education is growing as the world's population and cultures become more diverse. Teaching students about different cultures increases intercultural understanding. Socio-geographical factors influence the implementation of multicultural education and the level of intercultural sensitivity. This study is critical for exploring these relationships and improving intercultural education. Also, the aim of this research is to investigate the correlation between the prevalence of multicultural education and exposure to culture. This research uses correlation analysis methods to examine the relationship between multicultural educational practices and the level of intercultural awareness in a socio-geographical context. The research results show that there is a positive correlation between the implementation of multicultural education and students' intercultural awareness. The test results show a correlation coefficient of 0.63, indicating that the two variables are significantly related. Also, in the context of relationships between variables, multicultural education can increase understanding and appreciation of cultural diversity, while intercultural awareness enables inclusive interactions between individuals from different cultures.